Sequencing, single nucleotide polymorphisms identification and development of genotyping tests for leptin gene in zebu cattle - DUBEY, P P; SHARMA, ASHWANI; GOUR, D S; PRASHANT, PRASHANT; JAIN, ANUBHAV; MUKHOPADHYAY, C S; SINGH, AVTAR; KUMAR, DINESH (The Indian Journal of Animal Sciences, 2013)
The present study was undertaken with the objectives of sequencing of Bos indicus leptin gene and identification ofputative SNPs in entire gene. Nine novel SNPs and one reported SNP were identified in Sahiwal cattle population. Two polymerase chain reaction- restricted fragment length polymorphism (PCR-RFLP) tests were developed for SNP G to A in intron-1 and SNP C to T in exon-3 of leptin gene using DraI and MspI restriction enzymes, respectively. Allelic frequencies of G and A alleles were 71.29 and 28.71% and C and T alleles were 63.12 and 36.88% by DraI-RFLP and MspI RFLP, respectively, which reflects high variability, segregation of these putative DNA markers thus having ample scope of selection in this population. The MspI PCR-RFLP based DNA test for potential haplotype having 3 SNPs in exon-3 and the DraI DNA test with a single SNP in intron-1. Both newly developed DNA based tests and other identified SNPs could be of high relevance in association studies of Sahiwal zebu cattle of the region.